Artificial Intelligence Foundations: Thinking Machines. - Rose, Doug (linkedin.com, 2017)
Learn the key concepts behind artificial intelligence (AI), including strong and weak AI, approaches such as machine learning, and practical uses for new AI-enhanced technologies.